PHONOSEMANTICS: PHONEMES OF MODERN GREEK CAN EXPRESS INHERENT MEANINGS? - Tilikidou, Elpida (Sanata Dharma University, Yogyakarta, 2022)
There are four categories of phonological iconicity (sound symbolism or phonosemantics): lexical and non-lexical onomatopoeia (direct phonological iconicity), associative and phonaesthetic iconicity (indirect phonological iconicity). This paper focuses on the third category, the examples of indirect associative phonological iconicity with examples of onomatopoeic words from Modern Greek, which are connected with concepts that refer to acoustic but also to non-acoustic experiences. Indirect, associative connection of consonants and vowels with specific or abstract concepts is based on the phonological characteristics of these phonemes (sonority, manner of articulation, etc.).